Produção e caracterização estrutural e óptica de cerâmicas de YAG sinterizadas a laser e dopadas com Ce, Tb e Eu - Santos, Jerre Cristiano Alves dos (2016)
In this work, YAG ceramics were produced by the laser sintering technique with different dopant concentrations of Ce, Tb and Eu aiming the study of their structural and optical properties. The precursor powders were synthesized by the polymeric precursor method and the sintering of YAG was performed using a CO2 laser as a heat source. In order to characterize the samples, differential thermal analysis measurements, thermogravimetry, X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy and X-ray absorption were made. The optical measurements were performed by transmittance, photoluminescence, radioluminescence and thermoluminescence techniques. Initially, Ce-doped YAG samples presented a spurious phase. From these samples, a study of laser sintering was made, which allowed to establish a sintering route to the sequence of the work. Then, samples were obtained with different concentrations of Ce, Tb, and Eu presenting single phase. In laser sintering process a sample holder (base) was developed and allowed obtaining ceramics with good uniformity between center and edge of the ceramics and high relative density. The photoluminescence measurements exhibit the characteristic emission of the dopants. However, the europium doped samples showed the presence of Eu2+, as confirmed by XANES measurements. This fact was attributed to the sintering process that allowed the reduction of Eu3+ to Eu2+. The radioluminescent spectra also showed the characteristic emission of the activators ions. The TL curves of the samples showed that increasing dopant concentration there was a decrease in the number of defects responsible for the TL emission, and as consequence, a higher radioluminescent emission was observed with the increasing of the concentration of Tb and Eu. Additionally, the quenching phenomenon, increasing concentration in the samples doped with cerium, showed no direct relation with the capture of charges that contributed to the thermoluminescent phenomenon. Analysis of the EXAFS spectra showed that there was a decrease in the distance between the Eu and their nearest neighbors as concentration of Eu increase. This fact was attributed to the rapid cooling rate during sintering.